The Conceptual Framework of a Knowledge-Based Performance Management System - Dermawan Wibisono; Mohammed K. Khan (Gadjah Mada International Journal of Business, 2010)
Designing a Performance Management System (PMS) is anintegral part of management control systems. This paper presents ahybrid framework for the design of a PMS for the Indonesiancontext, and the tailor-made design is expected to overcome theshortcomings of earlier models. The present hybrid PMS modelseeks to improve the earlier research models using the followingnovel approaches: (1) implementation of a Knowledge-Based (KB)expert system, (2) Gauging Absences of Prerequisite (GAP) analysis, and (3) Analytical Hierarchy Process (AHP) methodology in anintegrated KBPMS. The paper shows that the present hybrid (KB-AHP-GAP) approach to developing a PMS model is a realisticmethodology. The combination of the KB-AHP-GAP approachallows detailed benchmarking of the PMS existing in an Indonesiancompany. Furthermore, this approach can assist in identifying andprioritising the key decisions that need to be executed to overcomethe existing PMS shortcomings.symbiotic strategic alliances. Con-versely, affiliate firms prefer competitive strategic alliances withcompetitors when they are not dependent on the parent firm.